2004
DOI: 10.1002/pen.20037
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of chaotic mixer design and operating conditions on morphology development in immiscible polymer systems

Abstract: Self‐similar mixing structures, a novel feature of chaotic mixing, were generated in this study as precursor to an array of mixing microstructures, such as nested layers, elongated fibrils, droplets and their combinations in the blending of two immiscible polymers, polypropylene (PP) and polyamide‐6 (PA6). Simulations based on Newtonian flow model were used to compute Poincaré maps and stretching distribution as the tools for investigation of the effect of shear gap and chaotic mixing parameter, such as angula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Figure 9 presents representative steady streamline portraits and sketches of steady velocity profiles obtained by boundary integral method. 12 Note that due to steady motion of the rotors, a majority of fluid elements travel on "circular trajectories" (Figure 9a) around the rotors and do not mix well. These trajectories become chaotic with time-periodic speed variation as given in Eqs.…”
Section: Chaotic Mixingmentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 9 presents representative steady streamline portraits and sketches of steady velocity profiles obtained by boundary integral method. 12 Note that due to steady motion of the rotors, a majority of fluid elements travel on "circular trajectories" (Figure 9a) around the rotors and do not mix well. These trajectories become chaotic with time-periodic speed variation as given in Eqs.…”
Section: Chaotic Mixingmentioning
confidence: 98%
“…A more detailed description of the experimental setup is provided elsewhere. 12 Chaotic fluid element trajectories were generated using a sine waveform for rotor motion…”
Section: Chaotic Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the chaotic mixing in the twin-screw or single-screw extruder has been carried out to reveal the stretching and folding actions, using Poincaré section, Lyapunov exponent, and so forth [8][9][10][11]. However, the studies of the tri-screw extruder are relatively limited due to its complex geometry and the short development time.…”
Section: Introductionmentioning
confidence: 99%
“…Favis investigated the effect of mixing time on the morphology development of blends of polypropylene and polycarbonate and concluded that the most significant changes in morphology occurred during the first 2 min of mixing when melting and softening of the materials was also occurring [31]. Jana studied the effects of viscosity ratio and composition on development of morphology in chaotic mixing of polymers [32,33]. Sundararaj studied the effect of compatibilization and rotation rate on the morphology development of polymer blends.…”
Section: Introductionmentioning
confidence: 99%